Case Analysis Malaysia British Assurance Bhd. Life Division - Yong, Koh Kok (2002)
MBA Life, the Malaysia minor insurer , is facing the critical problem with poor business performance. The economy recorded a poor financial performance even at Malaysia experienced economy good time in 1993 to 1996. Research being carry out to define the problem and looking for the solution. The feasibility study is to assist the company to setup its vision, mission and corporate objective.